A report of two cases of type 2 diabetes mellitus (T2DM): happy and longevity - Hemi Sinorita; Sri Sutarni; Abdul Gofir (Universitas Gadjah Mada, 2022)
Chronic hyperglycemia in patients with type 2 diabetes mellitus (T2DM) is associated with the development of complications and the increase of risk of mortality. Patients with T2DM have a shorter life expectancy than non-diabetic population. It is attributed to cardiovascular disease, stroke, renal disease, and infection. Depression secondary to T2DM worsens the quality of life. On the contrary, positive emotions correlated strongly with long life expectancy. A number of mechanisms might explain this correlation. We reported two geriatric patients over 80 y.o. with T2DM comorbidity for more than 20 years. Discussion point of these cases is the subject’s longer life span compared to the average diabetic patient’s life expectancy and great quality of life despite the disease burden of chronic hyperglycemia in T2DM and cardiovascular risk.